2008
DOI: 10.1073/pnas.0809677105
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants reduce endoplasmic reticulum stress and improve protein secretion

Abstract: Protein misfolding in the endoplasmic reticulum (ER) contributes to the pathogenesis of many diseases. Although oxidative stress can disrupt protein folding, how protein misfolding and oxidative stress impact each other has not been explored. We have analyzed expression of coagulation factor VIII (FVIII), the protein deficient in hemophilia A, to elucidate the relationship between protein misfolding and oxidative stress. Newly synthesized FVIII misfolds in the ER lumen, activates the unfolded protein response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
564
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 606 publications
(605 citation statements)
references
References 55 publications
34
564
2
2
Order By: Relevance
“…Furthermore, the relationship between oxidative stress and ER stress is a matter of debate, because activation of the UPR can also result in ROS generation [50][51][52]. In our study, we found that pro-oxidant Asc/Men treatment induced the translational control arm of the UPR (by enhancing eIF2 phosphorylation) and upregulation of ER folding capacity (by the increase in GRP94 protein, one of the major ER chaperones).…”
Section: Involvement Of Er Calcium Emptying In Er Stress Triggered Bymentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, the relationship between oxidative stress and ER stress is a matter of debate, because activation of the UPR can also result in ROS generation [50][51][52]. In our study, we found that pro-oxidant Asc/Men treatment induced the translational control arm of the UPR (by enhancing eIF2 phosphorylation) and upregulation of ER folding capacity (by the increase in GRP94 protein, one of the major ER chaperones).…”
Section: Involvement Of Er Calcium Emptying In Er Stress Triggered Bymentioning
confidence: 54%
“…These are still speculations and need further study. It has been proposed that BAPTA-AM interferes with Fenton's reaction [41,42] or may protect against a poorly defined pro-oxidative calciumassociated process, such as calcium-induced iron release [49] or ER stress-generated ROS production [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to point out that ER stress and impaired protein folding can lead to the production of a significant amount of ROS (Malhotra and Kaufman 2007; Malhotra et al. 2008). Interestingly, it is estimated that 25% of the ROS generated in a cell results from the formation of disulfide bonds in the ER during normal protein synthesis (Tu and Weissman 2004; Sevier and Kaiser 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One study investigated the expression of coagulation factor VIII, which is deficient in haemophilia A and is prone to misfolding in the ER (185) . It was found that factor VIII misfolding in the ER resulted in oxidative and ER stress in vitro in Chinese hamster ovary-(H9) cells with eventual apoptosis, which was attenuated by the addition of butylated hydroxyanisole, a phenolic, lipid-soluble antioxidant.…”
Section: Adipocyte Dysfunctionmentioning
confidence: 99%